Determinan Kinerja Dosen pada Pengajaran Metode Daring pada Masa Pandemi Covid-19 dengan Faktor Stres sebagai Pemediasi - Suryo Wibowo (Universitas Bunda Mulia, 2020)
The Covid-19 pandemic that hit the world, especially in Indonesia, apprently continued and still uncertain when completed. In early 2020 along with the emergence of this virus, the predicted impact of Covid-19 have been widely publicized in which various aspects will also be affected such as indonesia's economic growth decline, import disruption, aviation, tourism, and increased in food prices. In addition, this also has an impact on the education sector in Indonesia, especially in the lecture method in higher education. One impact is the change in the lecture method from the face-to-face method in the classroom to the online method. However, this is not necessarily successful. In the process many difficulties occur especially for lecturers. This study aims to analyse the determinants of the performance of college lecturers in Jakarta with stress factors in the use of online teaching technology. This study uses a quantitative method with a questionnaire instrument. The results of the study using SMART PLS 3.0 explain that both directly the performance of lecturers is influenced by workload factors that exist and the level of stress in the use of online teaching methods during this pandemic. In addition, this study also explains that Technostress as a mediating factor also explains the effect between workload on lecturer work performance. In the midst of conditions of rapid and limited change, training in the use of online teaching methods, especially in technical matters, is very much needed for lecturers to establish confidence in using online methods as well as the efficiency and effectiveness of switching from the face-to-face method in the class room to the online method.